Using Visualization Strategy to Improve Students Reading Skill in Comprehending Detailed Information - Santi, Melia; Reflinda, Reflinda (Modality Journal: International Journal of Linguistics and Literature, 2022)
The difficulty of students in understanding reading, especially finding detailed information still becomes the main problems in teaching reading. One of the solutions to break the problem is practicing visualization strategy in teaching reading.Â  Visualization strategy is recognized as one of the strategies that are effective and easy to apply in the teaching and learning process. The strategy is used to create their own images from the text in their minds. The image created in the minds of students is strongly influenced by their background knowledge. Strategies also help readers to find detailed information. This study aims to determine the application of visualization strategies to improve reading comprehension. This study applied a library research approach. Content analysis was used to analyze the data. This study found that visualization strategies can improve students' reading comprehension, especially in understanding detailed information.Kesulitan siswa dalam memahami bacaan, terutama menemukan informasi rinci masih menjadi masalah utama dalam pengajaran membaca. Salah satu solusi untuk memecahkan masalah tersebut adalah mempraktekkan strategi visualisasi dalam pengajaran membaca. Strategi visualisasi diakui sebagai salah satu strategi yang efektif dan mudah diterapkan dalam proses belajar mengajar. Strategi tersebut digunakan untuk membuat gambar sendiri dari teks dalam pikiran mereka. Citra yang tercipta di benak siswa sangat dipengaruhi oleh latar belakang pengetahuannya. Strategi juga membantu pembaca untuk menemukan informasi rinci. Penelitian ini bertujuan untuk mengetahui penerapan strategi visualisasi untuk meningkatkan pemahaman bacaan. Penelitian ini menggunakan pendekatan penelitian kepustakaan. Analisis isi digunakan untuk menganalisis data. Studi ini menemukan bahwa strategi visualisasi dapat meningkatkan pemahaman membaca siswa, terutama dalam memahami informasi rinci.